Magnetic-Hydrochar from Galam Bark Waste (Malaleuca cajuputi) as Sasirangan Waste Adsorbent - Habibah, Hanna; Ridwan, Risaldi; Safitri, Desmalina; Sunardi, Sunardi (ALKIMIA, 2022)
Galam wood (Malaleuca cajuputi) is one of the woody plants that is able to grow well in the peat swamp environment of the South Kalimantan wetlands. Research on the synthesis and characterization of magnetic-hydrochar from galam bark waste for the treatment of sasirangan liquid waste has been carried out. This study aims to determine the characteristics of hydrochar and magnetic-hydrochar against the adsorption ability of sasirangan liquid waste. The results showed that the modification of galam bark into hydrochar and magnetic-hydrochar produced different characteristics based on the analysis of functional groups of infrared spectra. The surface morphology of hydrochar and magnetic-hydrochar also showed the significant differences based on scanning electron microscope (SEM) analysis. The resulting magnetic-hydrochar showed a higher adsorption ability to sasirangan waste than the hydrochar of galam bark and galam bark without modification.